2000
DOI: 10.1536/jhj.41.713
|View full text |Cite
|
Sign up to set email alerts
|

Is the QT Interval an Indicator of Autonomic State?

Abstract: SUMMARYProlonged QT interval is suggested to indicate an increased risk of sudden cardiac death in certain clinical conditions such as diabetes mellitus. We investigated whether the individual QT interval is an indicator of an autonomic state. An ambulatory 24-hour ECG was recorded in 53 subjects from different clinical backgrounds. Power spectral components of heart rate variability (HRV) and the QT interval were regressively obtained at a heart rate of 60, 70, 80, 90, or 100 beats per minutes (bpm). Log valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
7
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…We noted no association between HF power of HRV and QTc interval and this is consistent with previous reports [34,40]. Recent work from Dewland et al has suggested that HRV and HRR yields information concerning distinct and independent aspects of cardiac parasympathetic regulation [13].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We noted no association between HF power of HRV and QTc interval and this is consistent with previous reports [34,40]. Recent work from Dewland et al has suggested that HRV and HRR yields information concerning distinct and independent aspects of cardiac parasympathetic regulation [13].…”
Section: Discussionsupporting
confidence: 93%
“…As such, the use of both noninvasive techniques may provide information on the relationship between QT interval and an integrated ANS that pharmacological dissection and ANS segregation cannot [34]. The purpose of this study was to examine the association between resting QT interval and noninvasive measures of cardiac autonomic function.…”
mentioning
confidence: 99%
“…The irregularity of the ventricular rhythm is considered to be caused by varying degrees of penetration of the atrial impulses into the AVN, which is mainly dependent on vagal tone during usual activity. 17,18 Therefore, our results would imply that AF patients with increased vagal tone have good exercise capacity. …”
Section: Discussionmentioning
confidence: 70%
“…In the other study by Curione et al [28], QTc interval and QTcdisp values were both considerably prolonged in IBD patients compared with individuals in the control group. The literatures suggested that sympathetic activity changes could be the reason for QT and QTc interval alterations and increased QT dispersion and QTc dispersion of ventricular repolarisation [29, 30]. In contrast to these studies, Dogan et al did not find any significant difference in QTdisp values between 69 IBD patients and controls [27].…”
Section: Discussionmentioning
confidence: 99%